Nursing assistance to a patient with falciform anaemia using the theoryof the basic human necessities and the icnp® version 1.0 - Furtado, Luciana Gomes; Nóbrega, Maria Miriam Lima da; Fontes, Wilma Dias de (Rev Rene, 2007)
It is a case study, carried out with a patient with Sickle Cell Anemia. The objective is the systematization of the nursing care to the light of the Horta’s Theory of the Basic Human Needs, using the ICNP® Version 1.0. In the analysis of the data the affected necessities were, the signals were grouped and the symptoms carried out the processes of diagnostic and therapeutically reasoning, of which the nursing diagnoses, the outcomes and the nursing interventions had emerged. They were so called according to ICNP® Version 1.0. The results evidenced that in the implementation of the assistance was possible in such a way to evidence the real necessities of the patient, what it allowed to intervene directly through the planning of the assistance, being this way, able to evaluate some expected results. It was observed that the use of a theoretical model associated the use of a system of nursing classification, which favors the accomplishment of a practical directed, reflexive assistance, bringing benefits in such a way to the customer as well as to the profession.